Worry processes in patients with persecutory delusions. (20th March 2016) - Startup, Helen; Pugh, Katherine; Dunn, Graham; Cordwell, Jacinta; Mander, Helen; Černis, Emma; Wingham, Gail; Shirvell, Katherine; Kingdon, David; Freeman, Daniel
Abstract : Objectives: Worry may be common in patients with paranoia and a contributory causal factor in the occurrence of the delusions. A number of psychological mechanisms have been linked to the occurrence of worry in emotional disorders but these are yet to be investigated in psychosis. The primary aim of the study was to test the links between five main worry mechanisms – perseverative thinking, catastrophizing, stop rules, metacognitive beliefs, and intolerance of uncertainty – and the cognitive style of worry in patients with persecutory delusions. Method: One hundred and fifty patients with persecutory delusions completed assessments of paranoia, worry, and worry mechanisms. Results: Worry in patients with psychosis was associated with the following: a perseverative thinking style, an 'as many as can' stop rule, a range of metacognitive beliefs (cognitive confidence, worry as uncontrollable and the need to control thoughts), and intolerance of uncertainty. Higher levels of worry were associated with higher levels of paranoia. There was also evidence that intolerance of uncertainty and the metacognitive belief concerning the need to control thoughts were independently associated with paranoia. Conclusions: Worry in patients with persecutory delusions may well be understood by similar underlying mechanisms as worry in emotional disorders. This supports the use of interventions targeting worry, suitably modified, for patients with psychosis. Practitioner points: Worry is a significant concern for patients with paranoia Worry in paranoia is likely to be caused by similar mechanisms as worry in emotional disorders The results support the recent trial findings that standard techniques for treating worry in anxiety, suitably modified, are applicable for patients with paranoia Limitations: The findings are limited by the self‐report nature of measures and by the study design which precludes any assumptions about the direction of causality between the psychological mechanisms and worry.